Studi Potensi Interaksi Obat pada Pasien Hipertensi di Puskesmas Wanasari Kabupaten Bekasi - Fajriatul Istiqomah; Widya Handayani; Rizky Farmasita; Norman Dyanto (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to identify and analyze potential Drug-Drug Interactions (pDDIs) in hypertensive patients at the Wanasari Primary Health Care, Bekasi Regency. Hypertension is a chronic disease with a high prevalence that often requires combination therapy, thus increasing the risk of drug interactions. This study used an analytical observational design with a retrospective approach to prescription data for hypertensive patients for the period August 2025. The sampling technique used was total sampling with a sample size of 82 patients who met the inclusion criteria. Identification of drug interactions was carried out using standard drug interaction references and classified based on pharmacokinetic and pharmacodynamic mechanisms, as well as minor, moderate, and major severity levels. The results showed that there were 105 potential drug interaction events with an average of 1.28 interactions per patient. Most interactions were categorized as moderate (86.6%) and dominated by pharmacodynamic mechanisms (55.2%). The most frequently found combination was amlodipine-dexamethasone (27%), while the most major interactions occurred in the combination of amlodipine-simvastatin (8%). Fisher's exact test showed no significant association between the number of medications and the drug interaction category (p > 0.05). This finding underscores the important role of pharmacists in prescription screening and therapy monitoring to improve medication safety in primary healthcare.